PORTFOLIO CONSIDERED AS A PROCESS ENHANCE COGNITION OF MATHEMATICS DISCIPLINES AT UNIVERSITY - Lyudmila S. Klentak (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article discusses the portfolio in terms of activation of the process of learning mathemati-cal disciplines at the university. We consider three main issues of knowledge: why, how and what to learn. The most constructive method of activation of knowledge at the present stage is to develop the student's portfolio, which reflects the ability to teach yourself. As part of the transition to a federal state educational standards of higher education, which declared the formation of the mandatory electronic student portfolios, including the preservation of the student work, reviews and evaluations of these work by all participants in the educational process, it follows that there is a need to use this innovative approach. Within the framework of the Bologna Declaration, to which Russia joined in 2003, we outlined the basic principles underlying the formation of a single European educational space, including ensuring con-sistency and comparability of the quality of education. Analysis of portfolio models used abroad, has shown that there is widespread demonstration, work and evaluation portfolio. This article presents the author's approach to the typology of the generalized student portfolio on mathematical disciplines, including all those kinds. We consider a student portfolio, consisting of seven main parts: basic information, an individual educational trajectory, the vector of development, creative activity, achievement, evaluation stage of formation of the portfolio, significant portfolio. The approach to the portfolio as a process of self-knowledge as a person to answer the questions: why, how and what to learn put student-oriented technology training.